Pengaruh Jumlah Pakan Terhadap Produksi Udang Vannamei di Desa Duduklor Kecamatan Glagah Kabupaten Lamongan - Sa'adah, Wachidatus (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Vannamei shrimp (Litopenaeus vannamei) cultivation in Lamongan Regency is a rapidly growing fisheries sector, with high demand in domestic and international markets. Research on the effect of feed quantity on vannamei shrimp production in Duduklor Village is expected to provide recommendations to improve cultivation efficiency and productivity in the fisheries sector. This research is a quantitative study with a purposive sample method in selecting its samples, and using correlation and regression analysis calculations. The results of the study obtained tcount> ttable = 11.01> 2.571, so that the H0 testing criteria were rejected and Ha was accepted because tcount> ttable, which means there is an influence between the amount of feed. Then the r value of 0.98 can be interpreted that the value indicates a very strong relationship between the amount of feed and vannamei shrimp production. Likewise with the constant value of -25.45, and the coefficient value of 1.04, it means that there is an influence between the amount of feed and vannamei shrimp production.